2002
DOI: 10.1007/s11745-006-0982-3
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with a pine bark extract rich in polyphenols increases plasma antioxidant capacity and alters the plasma lipoprotein profile

Abstract: Pycnogenol (PYC), an extract of French maritime pine bark (Pinus pinaster), is a potent antioxidant with potential health benefits. Its bioavailabilty has previously been shown by urinary excretion studies of constituents and metabolites of PYC. The aim of this study was to test the effect of PYC supplementation on measures of oxidative stress and the lipid profile in humans. Twenty-five healthy subjects received PYC (150 mg/d) for 6 wk. Fasting blood was collected at baseline, after 3 and 6 wk of supplementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
111
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(119 citation statements)
references
References 29 publications
3
111
1
4
Order By: Relevance
“…In addition, HDL-cholesterol levels were significantly increased by Pyc supplementation. Devaraj et al reported similar results, in that Pyc supplementation (150 mg/d) for 6 wk significantly reduced low density lipoprotein (LDL)-cholesterol and increased HDL-cholesterol concentrations in the plasma of 25 healthy subjects (28). Taken together, these results suggest that Pyc might play a beneficial role in obesityrelated diseases by improving lipid profiles.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, HDL-cholesterol levels were significantly increased by Pyc supplementation. Devaraj et al reported similar results, in that Pyc supplementation (150 mg/d) for 6 wk significantly reduced low density lipoprotein (LDL)-cholesterol and increased HDL-cholesterol concentrations in the plasma of 25 healthy subjects (28). Taken together, these results suggest that Pyc might play a beneficial role in obesityrelated diseases by improving lipid profiles.…”
Section: Discussionmentioning
confidence: 65%
“…26 The slight lowering of cholesterol, observed in this study as well as in clinical trials with Pycnogenol, may contribute to an anti-atherosclerotic effect. 6,27,28 All other parameters of routine clinical chemistry remained in the normal range. The small, but significant increase in the number of erythrocytes and in the concentrations of albumin and hemoglobin remained well within the reference ranges for male adults.…”
Section: Discussionmentioning
confidence: 89%
“…An additional mechanism by which animals could be exposed to an increased concentration of dietary polyphenols or other phytochemicals is through a change in the type of plant being consumed. Bark, for example, is a rich source of polyphenols [41,42] but is unlikely to be selected until other food choices have been exhausted. In fact, many polyphenols appear to play specific roles in making plants less palatable to deter herbivores and insect pests [20] , so it is possible that higher polyphenol content is a general property of less desirable plant foods.…”
Section: Introductionmentioning
confidence: 99%